THE GROWTH AND YIELD RESPONSE OF GREEN MUSTARD TO THE CALM SHELL POWDER APPLICATION ON PEAT SOIL - ., Junardi; ., Rahmidiyani; Hadijah, Siti (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aimed to determine the best dosage of clam shell powder for the growth and yield of green mustard on peat soil. The research was conducted at the research field of Agricultural Faculty of Tanjungpura University Pontianak from October 28th to December 28th 2018. The Completely Randomized Design (CRD) was used in this experiment with 4 levels of clam shell powder dosage and 6 replications. The levels of dosage were 10.1, 13.6, 17.3 and 20 tons/ha consecutively. Observed variables were the leaf number, the root volume, the leaf area and the fresh and dry weight of plant. The results showed that the levels of clam shell powder had no significant effects on all of growth and yield variables observed. It is concluded that the 10.1 tons/ha was the most efficient dosage of clam shell powder. Keywords : the clam shell powder, peat soil, Green Mustard